Animal health constraints of dairy goats kept under smallholder farming systems in Kongwa and Mvomero Districts, Tanzania - Shija, D.S.N.; Kusiluka, L.J.M.; Chenyambuga, S.W.; Shayo, D.D.; Lekule, F.P. (Academic Journals, 2014)
This study was conducted to determine animal health constraints for dairy goats kept by small-scale farmers in Kongwa and Mvomero districts, Tanzania. A total of 129 dairy goats belonging to 108 farmers were screened for gastrointestinal nematode (GIN) infection, coccidiosis, haemoparasites, brucellosis and contagious caprine pleuropneumonia (CCPP) over a period of 11 months. Other clinical diseases and mortalities were recorded. The goats used were Norwegian crosses and Toggenburg crosses. The mean prevalence of GIN infection and coccidiosis in all goats were 54.8 and 57.4%, respectively. Prevalence of GIN infection was higher (P ≤ 0.05) during the rainy months than in the dry months, but the prevalence of coccidiosis did not differ (P > 0.05) between the dry and rainy seasons. The EPG in goats did not differ (P > 0.05) between Kongwa (169.79 ± 0.03 EPG) and Mvomero (171.51 ± 0.04 EPG) districts, but the OPG differed significantly (P ≤ 0.05) with values of 793.15 ± 0.04 (Kongwa) and 364.02 ± 0.05 (Mvomero). The prevalence of CCPP in the goats was 26.4%. Other clinical diseases included respiratory diseases, infectious keratoconjunctivitis and orf (scabby lesions around mouth and nostrils). Both tests for haemoparasites and brucellosis indicated negative results for all goats tested. Mortality rate during the study period was 15.5% and the major causes of deaths were respiratory diseases, bloat and food poisoning. In conclusion, gastrointestinal nematodes are prevalent in both districts, but the burdens are relatively low to justify mass treatment. The Norwegian goats are more susceptible to GIN infection and coccidiosis compared to Toggenburg goats.